Transformasi Kehidupan Rasul Paulus dalam Melayani Tuhan dan Kontribusinya Bagi Pembentukan Mahasiswa STTAB (Sekolah Tinggi Teologi Arastamar Bengkulu) - Wendy Efriduansyah Situmorang; Fajarman Halawa; Ellisa Oktavia (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
Paul was a figure who initially hated Christianity, in fact Paul was ethically and morally a criminal based on religion. In fact he was a religious figure from the Jewish religion but he killed people who followed Jesus. However, behind Paul's crimes, before he converted, he experienced a personal encounter that changed his life completely. Paul experienced a very, very radical life transformation because at first he really wanted to destroy the people who followed Jesus, but instead he risked his own life to educate his life in preaching the Gospel of Jesus Christ. The author uses literature-based research methods sourced from books and several journals, thereby helping the author to analyze the life of the apostle Paul and the life of theology students in the dormitory. Every theology student must experience a life transformation, because there are many young people who lived their past lives from different backgrounds or were not morally good, but on campus theology must change. So the author also believes that there are many theology students who struggle with ethics, generally theology students have a background far from the church but instead become servants of God. Formed in dormitory life and disciplined in life spiritually and morally.